Implementasi Akuntansi Murabahah terhadap Pembiayaan Kepemilikan Rumah pada Perbankan Syariah - Nurliza Lubis; Ainul Yusna Harahap; Fathia (Jurnal Penelitian Ekonomi Akuntansi, 2023)
The purpose of this study is to find out how murabahah accounting is applied to Islamic banking, especially Bank Aceh Syariah Kota Kualasimpang. This study applies qualitative descriptive analysis. Data was collected through interviews with company employees and finance teams that handle homeownership financing, and documentation such as financial statements and literature. Qualitative descriptive analysis is used to analyze the data obtained. The results of the study show that Bank Aceh Syariah Kota Kualasimpang has not implemented murabahah accounting fully by the concept of Islamic accounting. In the results of the study, the bank did not set fines for customers who were late in paying financing, both when admitting and calculating fines. The limitation of this study is that the results are difficult to generalize broadly because the research is only based on research studies on one Islamic bank. So that the next researcher can add the amount of research to other Islamic banking so that the results of the research can be widely generalized.